Forest Structure, Diversity and Dynamics in Terra Firme and Igapó Gallery Forests in the Colombian Orinoco Basin - Juan S. González-Abella (MDPI AG, 2021)
Studies of dynamics and biomass accumulation are essential for understanding forest functioning and productivity. They are also valuable when planning strategies for the conservation and sustainable use of natural resources. This study was conducted in five one-hectare plots of gallery forest in the Orinoco basin (three in terra firme and two in igapó floodplains), located in the Tomogrande Reserve, Santa Rosalía municipality, Vichada, Colombia. The differences between these forest types were determined and quantified considering diversity, floristic composition, aboveground biomass, forest dynamics and the influence of soils’ physicochemical composition. Terra firme forests were more diverse (Fisher’s α = 30.4) and had higher mortality and recruitment rates than igapó forests but there were no significant differences in stem turnover rates between forest types. Relative tree growth rate was also higher in terra firme than in igapó, but the opposite was found for biomass change (1.47 t/ha/year in igapó), resulting in an average carbon accumulation rate of 0.33 t/ha/year in terra firme and 0.66 t/ha/year in igapó. Igapó forest has high carbon accumulation potential given the high wood density of certain dominant species. Igapó soils contained a higher concentration of sand, silt, phosphorus and potassium ions, while terra firme soils had a higher clay content with lower pH. In general, the demographic and growth rates were consistent with those described for Amazonian forests. This study highlights the potential of igapó forest in the Orinoco basin as important carbon sinks, which should be included in the management and conservation strategies for this region.